VPN SITE TO SITE IMPLEMENTATION USING PROTOCOL L2TP AND IPSEC - Santoso, Budi; Sani, Asrul; Husain, T; Hendri, Nedi (Department of Computer Engineering, Universitas Wiralodra, 2021)
Data exchange communication has developed, which leads to centralized communication, and to achieve this communication requires a type of data communication whose data is accommodated on the server and can be accessed by clients, such as at organization. As a company engaged in education, the development of centralized data communication by utilizing the intranet network has been formed. The use of an intranet network allows data communication that is vulnerable to wiretapping. To fix this using a VPN network. L2TP and IPsec VPNs have different performances, especially in the level of security provided. In this study, an analysis of the L2TP and IPsec VPN network performance was carried out on the SMB Server on the Ubuntu server and the Mikrotik router for its VPN configuration. In this study, the L2TP and IPsec VPN was designed by configuring the Mikrotik RB 450G router and the SMB Server configuration using Command Line Interface on Ubuntu 18.04 server. For security analysis, use hacking methods to get VPN Server login data and sniffing methods to get SMB Server login data and SMB data. For performance analysis using parameters of delay, throughput, and packet loss. Wireshark is software for checking by capturing each packet of data from an interface. The research objective to be achieved is to design a VPN technology based on L2TP & IPSec, to be able to determine the resulting performance after implementing a VPN based on L2TP & Ip Sec. The result is that VPN can connect from HO to branch one and branch two or connect from public connection to local connection. The Ubuntu server used is also running well, so it helps the VPN process properly.